Mouse model of DNCB-induced atopic dermatitis - Alshammari Fanar Hamad; Jong-Hun Han; Irfan Ahmad Rather (Bangladesh Pharmacological Society, 2017)
Atopic dermatitis is a skin disease characterized by allergic skin inflammation, redness and itching. The animal model is necessary to find out new drugs. The DNCB-induced animal model of atopic dermatitis includes the following steps: 1) Selection of animals; 2) Shaving of dorsal skin; 3) Applying DNCB once in 24 hours for three days; 4) Monitoring the development of atopy on day 4 post DNCB application. Further, the efficacy of reference drug can be determined by applying on the atopy skin, depends on the nature and aim of the work. Video Clip of Methodology: 8 min   Full Screen   Alternate